The counterpoint in the Cumanana and the Andahuaylino carnaval (Pukllay taki) - León Soncco, Dionicia (2021)
In Peru, due to its cultural and geographical diversity, a wealth of manifestations can be found throughout its territory, thus we find artistic expressions linked to each people, each culture. Some similar and other unique that have remained in the collective memory of its people,since they are transmitted from generation to generation and are kept alive, thanks to the families that cultivate art or the institutions that promote it.In the case of Andean and Afro-Peruvian oral tradition literature, which also constitute part of the cultural heritage of our country, we find some peculiarities among the various oral and musical expressive forms.A comparison will be made between the counterpoint in the cumanana and in the Andalusian carnival verses (pukllay taki), because certainsimilar characteristics can be seen in their composition and interpretation.